Nature and operation of local cable networks in Miag-ao and Janiuay, Iloilo as they adhere to NTC rules and regulations as they serve their subscribers. - Aspa, Ma. Edevae; Deferia, Mary Gold.; Umadhay, Julie-Ann.
Cable Antenna Television or cable television is a system wherein TV signals are transmitted from the feeding satellites to the receivers by means of a centralized system called Head End., This study is about the two local cable networks in the province of Iloilo, namely, southern Iloilo Cable Incorporated in Miag-ao and Oway Cable Ventures Incorporated in Janiuay. The study aims to know the nature and operation of the local cable networks in Miag-ao and Janiuay. It aims to find out the similarities and differences of the said local cable networks, and determine if these local cable networks follow the rules and regulations set by the National Telecommunications Commission (NTC).Purposive sampling, a type of non-probability sampling that uses respondents who best meets the purpose of this study, is used. The station managers are allowed to select the respective subscribers to be surveyed for the purpose of getting the exact location of their coverage, to know the condition of the reception, and the perception of the subscribers on the said local cable network in the municipality. In analyzing the data gathered, the researchers used frequency counts and percentage . Results show that the subscribers of Southern Iloilo Cable Incorporated in Miag-ao were not satisfied with the services offered by the local cable netwrok in the municiplaity. Meanwhile, the subscribers in Janiuay were satisfied with the services offred by Oway Cable Ventures Incorporated.
Thesis (Undergraduate, Bachelor of Arts in Broadcast Communication) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Cable networks -- Janiuay, Iloilo; Cable networks -- Miag-ao, Iloilo